Factors influencing the selection of higher learning private institutions among students in Malaysia - A.Nagarajah, Sivasanggiri (2020)
The objective of this study is to examine the factors influencing the selection of higher learning private institutions among students in Malaysia. There are three variables identified which influences the students choice of private institutions which are institutions reputation, cost of education and influence of family and peers. Quantitative analysis approach was used in this study and the instrument is questionnaire, distributed through email. There were 200 respondents involved from the students of various private institutions in Malaysia. The Pearson correlation and multiple regression technique were used to explain the results. By implementing these findings, marketing team would be able to identify new marketing plans to improvise and increase the number of enrollments in their respective institutions. Based on the study, cost of education is the main factor of students‟ selection of private institutions of higher learning in Malaysia, followed by university reputation and the last one is influence of family and peers.